2016
DOI: 10.1186/s13075-016-0995-0
|View full text |Cite
|
Sign up to set email alerts
|

Baseline CXCL10 and CXCL13 levels are predictive biomarkers for tumor necrosis factor inhibitor therapy in patients with moderate to severe rheumatoid arthritis: a pilot, prospective study

Abstract: BackgroundTNF inhibitors have been used as a treatment for moderate to severe RA patients. However, reliable biomarkers that predict therapeutic response to TNF inhibitors are lacking. In this study, we investigated whether chemokines may represent useful biomarkers to predict the response to TNF inhibitor therapy in RA.MethodsRA patients (n = 29) who were initiating adalimumab or etanercept were recruited from the rheumatology clinics at Cooper University Hospital. RA patients were evaluated at baseline and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 34 publications
2
29
1
2
Order By: Relevance
“…Whether the induction of CXCL9 by TNF-α requires cooperation of other factors, such as IFN-γ, during the development of SS will be addressed in our future investigations. In addition to CXCR3 ligands, CXCL13 is a critical chemokine directing B cell recruitment to target organs in inflammatory conditions 44 and the decrease in CXCL13 expression resulting from the anti-TNF therapy is considered a potential predictive biomarker in rheumatic arthritis patients 45 . In line with these findings, we demonstrated that neutralization of TNF-α leads to down-regulation of CXCL13 expression also in SS disease settings.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the induction of CXCL9 by TNF-α requires cooperation of other factors, such as IFN-γ, during the development of SS will be addressed in our future investigations. In addition to CXCR3 ligands, CXCL13 is a critical chemokine directing B cell recruitment to target organs in inflammatory conditions 44 and the decrease in CXCL13 expression resulting from the anti-TNF therapy is considered a potential predictive biomarker in rheumatic arthritis patients 45 . In line with these findings, we demonstrated that neutralization of TNF-α leads to down-regulation of CXCL13 expression also in SS disease settings.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, higher serum levels of CCL22 in patients with RA compared to healthy controls have been reported previously; however, in that study, the majority of the patients were treated with DMARD and there was no information concerning the disease duration [22]. Various treatments have been shown to affect the levels of chemokines in the circulation [15][16][17][18], which suggests that evaluation of chemokines in untreated patients might be advantageous.…”
Section: Discussionmentioning
confidence: 69%
“…Similarly, in another cohort with pre-patients and early RA patients in which blood chemokines were investigated, 39% of the patients were treated with prednisolone [14]. Treatment with biological and non-biological DMARD in RA have been shown to alter the chemokine levels in the blood [15][16][17][18], suggesting a need to evaluate chemokines in a pure group of DMARD-naive ueRA patients.…”
Section: Introductionmentioning
confidence: 99%
“…Immune effects of filgotinib were also captured with key T-cell, B-cell, and innate cell cytokines and their recruiting chemokines, together with a cell-based biomarker readout of major immune cell subsets in the blood by flow cytometry immunophenotyping. Pathogenic effectors of tissue matrix damage and cross-talk between synovial fibroblasts, endothelial cells, cartilage, and bone were founded on a clinically validated panel of soluble biomarkers that associate with RA disease activity [1,11]. Finally, several biomarkers that have been implicated in predicting clinical therapeutic response were also included [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenic effectors of tissue matrix damage and cross-talk between synovial fibroblasts, endothelial cells, cartilage, and bone were founded on a clinically validated panel of soluble biomarkers that associate with RA disease activity [1,11]. Finally, several biomarkers that have been implicated in predicting clinical therapeutic response were also included [11,12]. By using highly sensitive multiplex immunoassays that minimized sample blood volume burden to patients, we could profile serial time points for an extensive characterization of a new molecular entity in the next generation of targeted RA therapeutics.…”
Section: Introductionmentioning
confidence: 99%